Modeling Secured Certificate Mechanism with Cloud Services - Ghazali, Osman; Ali, Norazila; Ta'a, Azman; Din, Roshidi (UUM, 2021)
A certificate of graduation is one of the most important documents for the graduate. It is proof of a qualification that will be used in applying for a job or promotion. Therefore, many certificates have been created authentically and altered to falsely make an impression that the bearer is a high achiever. The advancement of technologies in photocopying and printing has caused some problems for employers or other stakeholders because fake certificates can be easily created as good as the original copy. Furthermore, it is hard to differentiate the genuine certificate, although the prominent educational institution has issued the original to the graduates. Sometimes, some factors caused inefficiency in the university's operational services, which had affected the verification process of academic certificates and documents. It is essential for the university or educational institution to provide an easy way to verify the certificate's genuine and its source, whether it is a fake, altered or original certificate. This study proposed a certificate verification model which will provide the solution to ease the certificate verification process. The proposed model ensures the certificate's validity by providing a simple verification process and ensuring the graduate data's confidentiality by giving the graduate the right to approve or disapprove a request to verify and request to view the graduate certificate. A prototyping approach has been used for application development and evaluation. The model has been implemented and evaluated as a cloud-based/web-based system for certificate verification. The prototype has been demonstrated to selected UUM's students for evaluation, and the demonstration they are asked to answer a questionnaire. The result shows that the system the respondents agree on efficiency, perceived trust, perceived ease of use, perceived usefulness, perceived usability, and perceived user satisfaction. This indicates that the certificate verification model can be a solution for universities to address fake or unauthentic certificate problems.